Toward Integrated DoD Biosurveillance Assessment and Opportunities - Moore, Melinda (RAND Corporation, 2013)
In the context of the 2012 National Strategy for Biosurveillance, the Office of Management and Budget asked the Department of Defense (DoD) to review its biosurveillance programs. DoD biosurveillance supports three strategic missions and four desired outcomes. More near-real-time analysis and better internal and external integration could enhance its performance and value. Improvements are needed in key enablers, including funding.